Analisa Keputusan Menabung di Bank Mega Syariah di Kota Medan - Athifah Zalfa Lesmana; Syafrida Hafni Sahir (ARBITRASE: Journal of Economics and Accounting, 2023)
The purpose of this study is to determine the impact of religiosity, reference groups, and motivation on saving decisions at the Bank Mega Syariah Iskandar Muda Branch in Medan. The research method employed is quantitative, with an explanatory survey approach. The data is obtained directly from the respondents using a primary data collection technique and a questionnaire was used as the research instrument. The data analysis technique used is multiple linear regression which is processed by using SPSS 24. The sampling method used was accidental sampling with a total of 70 Bank Mega Syariah customers. Based on the results of the analyses, religiosity had partially positive and significant effect on the Saving Decision, the Reference Group had no and insignificant effect partially on the Saving Decision, and Motivation had partially positive and significant effect on the Saving Decision.